PENGARUH PEMBELAJARAN MEDIA VISUAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VII A & B MTS AL AHSAN di TANAH SAREAL KOTA BOGOR - Anshori, Fadiyah; Indriya, Indriya; Muhyani, Muhyani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the effect of using visual media on students' learning outcomes in the Akidah Akhlak subject for seventh-grade students at MTs Al Ahsan Bogor. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of two classes: the experimental class, which received lessons using visual media in the form of PowerPoint slides, and the control class, which used conventional teaching methods. Data collection was conducted through pre-tests and post-tests, and the results were analyzed using a t-test with the help of SPSS software. The findings indicate a significant improvement in student learning outcomes when visual media is used compared to conventional methods. The average post-test score for the experimental class reached 94.30, while the control class only scored 65.47. The t-test results showed a significance value (2-tailed) of 0.000 < 0.05, indicating a significant difference between the two groups. Thus, the use of visual media is proven to be effective in enhancing students' comprehension and learning outcomes. These findings reinforce that visual media can clarify learning materials, increase student motivation, and assist in understanding concepts more effectively. This research is expected to serve as a reference for educators in selecting more innovative and interactive teaching strategies to improve the quality of education